Trafficking and global crime control - Lee, Maggy (Sage Publ., 2011)
Contested definitions of human trafficking -- Contemporary patterns of human trafficking -- Constructing and denying victimhood in trafficking -- Trafficking and transnational organised crime -- The war on human trafficking -- Transnational policing in human trafficking -- Rethinking human trafficking -- Appendix. Timeline : key international conventions and national legislation against human trafficking ; Useful websites